2013
DOI: 10.1016/j.neuro.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential response to acrylonitrile toxicity in rat primary astrocytes and microglia

Abstract: Acrylonitrile (ACN) is a widely used chemical in the production of plastics, resins, nitriles, acrylic fibers, synthetic rubber and acrylamide. While acute high level exposures to ACN are known to be lethal, chronic low dose exposures causes glial cell tumors in rats. Recently, these glial tumors have been characterized as microglial in origin. While effects of ACN on astrocytes, the more numerous glial cell, have been investigated, the effects on microglia are unknown. This study was conducted to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…3d). This enzyme is expressed and active in Acrylonitrile [157] Ammonium [90,158] Anethole dithiolethione [159] Arsenite [91] Arsenate [89] Cadmium chloride [89,91] Catalpol [160] Copper chloride [89,92] Copper oxide nanoparticles [93] Curcumin Thyroid hormone [169] This [78][79][80]. In addition to Mrp1, astrocytes express a number of other Mrps and other potential GSH exporters in culture and in vivo [43, [81][82][83][84][85][86], but the contribution of these transporters in astrocytic export processes remains to be elucidated.…”
Section: Gsh Redox Cyclingmentioning
confidence: 99%
“…3d). This enzyme is expressed and active in Acrylonitrile [157] Ammonium [90,158] Anethole dithiolethione [159] Arsenite [91] Arsenate [89] Cadmium chloride [89,91] Catalpol [160] Copper chloride [89,92] Copper oxide nanoparticles [93] Curcumin Thyroid hormone [169] This [78][79][80]. In addition to Mrp1, astrocytes express a number of other Mrps and other potential GSH exporters in culture and in vivo [43, [81][82][83][84][85][86], but the contribution of these transporters in astrocytic export processes remains to be elucidated.…”
Section: Gsh Redox Cyclingmentioning
confidence: 99%
“…34−36 While astrocytes and neurons are the major cell types of the central nervous system, microglia are a counterpart to macrophages and act as the major inflammatory cell of the brain and spinal cord by removing damaged neurons and pathogens. 26,37 Microglial cells have an important role in extracellular signaling and also respond to neuronal injury by releasing neurotoxic and neurotrophic factors. All these processes can be modulated by oxidative stress, compromising microglial function and homeostasis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, these emerging pollution sources are highly toxic, carcinogenic (Ramakrishna et al 1989; Thier et al 2000; Quast 2002) and related toxicity investigation has been widely reported, e.g. acrylonitrile could leads to neurobehavioral disorder in rats and some human sicknesses (Caito et al 2013; Khan et al 2009; Tanii and Hashimoto 1984). So it is urgent to explore safe and efficient treatment technology on acrylonitrile wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%